Characteristics of Karst Formations and Their Significance for Shale Gas Exploration - Hu, Xiuquan; Liu, Hong; Tan, Xiucheng; Dan, Yong; He, Heng; Xiao, Chenjing; Li, Ruixue (Frontiers in Earth Science, 2022)
The classification method of karst formations is widely used in engineering geology and environmental geology, but it is seldom used in petroleum geology. In this study, the division method of karst formations is applied to the sealing study of shale gas roof and floor carbonate rocks, and then the influence on shale gas accumulation and drilling is discussed.The Paleozoic black shale in the southern China is mainly formed by Marine faces and transitional faces, the intergrowth between shale and carbonate rocks is a basic geological feature of the Paleozoic strata in the southern China. In practical exploration, carbonate karst is one of the unavoidable problems in shale gas exploration in Southern China. Around the black shale target layer, upper palaeozoic trait region, the paper starts from the development strength of karst strata, through geological profile survey, spring flow statistics, test and other methods and means, the shale and the carbonate rock contacted with it are taken as a whole to explore the impact of karst strata on shale gas drilling. The upper Paleozoic karst strata in the study area are divided into 2 kinds, 4 types and 6 subtypes. It is determined that the limestone continuous karst strata of the Sidazhai Formation and the second member of the Nandan Formation are the sensitive layer of the shale gas drilling, while the first number of Nandan Formation and the Wuzhishan Formation are the shale reservoir-forming packers. In addition, the evaluation method of the karst sensitivity of shale gas exploration is summarized. For the study area, the karst avoidance area, karst sensitive area and karst insensitive area of shale gas exploration are divided. Combined with the surface and underground conditions, and the basic geological conditions of shale gas are not significantly different, shale gas drilling should avoid the fold core and fault zones.